MENINGKATKAN KETERAMPILAN MENULISKAN KEMBALI KARANGAN DENGAN MODEL KOOPERATIF CIRC SISWA KELAS VII SMPN 4 KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Emzimur Emzimur (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is motivated by the low results of writing skills of grade VII students of state SMPN 4 KuantanMudik Kabupaten Kuantan Singingi. The purpose of this study is to improve the results of the process andevaluation of students' writing skills. This study uses classroom action research which consists of two cycles. Theresults of data analysis, the students' writing process skills for each indicator, in learning 1 cycle I is 70.8 withgood categories. The results of the assessment process of writing skills at the 2nd meeting is 78.2 with goodcategories. While the results of writing skills at the 3rd meeting of the second cycle were 86.6 with very goodcategories. At the 4th cycle II meeting was 93.2 with a very good category. The average of the results of theassessment process of writing skills is 81.65 with very good score. in the basic score, students who completedwere only 11 students with a percentage of trajectories of 55% in the unfinished category. In the first cycle thelearning outcomes of students increased to 14 students who were complete with a percentage of 70% with thecategory incomplete. Learning outcomes of students in the second cycle, again showed an increase with thenumber of students who reached the minimum completeness criteria of 18 students with completeness as big as90% complete category. With this result, the researcher can conclude that, by applying the CIRC learningmodel, it can improve the results of writing skills of students in class VII SMPN 4 Kuantan Mudik KabupatenKuantan Singingi.